Enhancing educational continuity: exploring factors affecting the success of learning management systems in Dubai higher education - Allam, Hesham; Dempere, Juan; Kalota, Faisal; Hua, David (Frontiers in Education, 2024)
Introduction In recent years, educational institutions worldwide have increasingly embraced technology as a means of enhancing the learning experience and adapting to the demands of the modern era. This trend toward digital transformation has become even more pronounced in the wake of the COVID-19 pandemic, which necessitated a rapid shift to remote learning modalities. Learning Management Systems (LMS) have emerged as crucial tools for educational continuity, enabling institutions to deliver course materials, facilitate communication, and manage student progress in virtual environments. However, the success of LMS implementation varied among educational institutions, with some achieving seamless transitions while others encountered challenges stemming from students' reluctance to fully embrace the technology. This paper contributes to the understanding of LMS adoption in higher education institutions in Dubai, UAE, by proposing a comprehensive model based on the Technology Acceptance Model (TAM) and enhanced with modern factors that fit the nature of virtual learning. Methods Employing a quantitative research approach, the study utilized the main structure of the Technology Acceptance Model (TAM) to propose an enhanced version of factors that might influence students' acceptance of online learning management systems. To collect the necessary data, a self-administered survey questionnaire was distributed to 500 students, ensuring a comprehensive dataset for analysis. The analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM), a robust statistical technique suitable for complex models with latent variables. This method allowed the researchers to empirically validate the proposed model, assessing the impact of various modern factors tailored to the nature of virtual learning environments. Results The study's empirical findings revealed several significant factors influencing students' intentions to use LMS, including personal innovation, perceived utility, system quality, service quality, and information quality. While system quality encompasses the technical aspects and functionalities of the LMS, information quality focuses on the relevance, accuracy, completeness, and timeliness of the system's content. Discussion These insights provide valuable guidance for educational institutions in Dubai and beyond, offering actionable recommendations for optimizing LMS implementation strategies to enhance student engagement and educational outcomes in the digital learning landscape.